(untitled) (Revista de Ensino em Artes, Moda e Design, 2020)
The production of images is part of the evolution of humanity, as well as, it is clo- sely linked to the act of telling stories. Images, especially photographic ones, configu- re a powerful form of communication, since visual messages stimulate emotional and intellectual responses, that is, they allow feeling and reflecting on a certain subject. In this sense, understanding the relationship between narrative and digital photography is fundamental to enhance the visual and imagery language, especially in the educa- tion of professionals, such as designers, who use photography as a constant resource. Therefore, this study aimed to identify current research that addresses issues about the narrative in the processes of reading and writing photographic images. For that, a systematic literature review was adopted as a method. From the results achieved in this process, it is possible to state that the studies focus on three main axes: as for the narrative created by collection, that is, the narrative produced by a sequence of ima- ges; as for the narrative composed in a single still image; and as to methods and inno- vations in photographic representation. In the end, it is evident that the small number of publications involving strategies that foster the development of reading and writing skills of photographic images associated with narratological studies indicate a need to expand research on this theme.